The Influence of Company Size, Business Risk, and Sales Growth on Capital Structure Mediated by Profitability - Yulianti, Anisa; Jihadi, Muhammad; Nurjannah, Dewi (Universitas Muhammadiyah Malang, 2024)
This study aimed to determine the effect of company size, business risk, and sales growth on capital structure with profitability as an intervening variable on the JII stock index on the Indonesia Stock Exchange (IDX) from 2017 to 2021. The method used to determine the research sample is purposive sampling. The source of data in this research is secondary data. Data analysis techniques used path analysis, t-test (partial), and Sobel test (mediation) using SPSS version 23. The study's results stated that company size, sales growth, and profitability have a significant effect on capital structure while business risk has no significant effect on capital structure. Company size, business risk, and sales growth significantly affect profitability. The Sobel test results state that company size, business risk, and sales growth have a significant effect on capital structure mediated by profitability, meaning that mediation occurs.